Preservation of Regional Languages (Sundanese Wewengkon Pandeglang) through Teaching Materials with Local Wisdom - Amilul Ulum, Uyung; Hidayat, Sholeh; Leksono, Suroso Mukti; Jamaludin, Ujang (Nashir Al-Kutub Indonesia, 2023)
This study aims to analyze efforts to maintain Sundanese language wewengkon Pandeglang as a characteristic of the Sundanese speech community in areas where Sundanese is used, which are spread across the two provinces of West Java and Banten. Pandeglang Sundanese language is distinctive or unique with all the values ​​contained in it. The method used is qualitative-descriptive. The data studied is in the form of teaching material documents as a language construct that represents the speech group of Sundanese Pandeglang. As a result, the Sundanese wewengkon Pandeglang is used in the form of vocabulary which is inserted into parts of teaching materials whose structure is Reading, Pedaran, Kaparigelan, Pangaweruh Sundanese, and Purwakecap. Thus it can be concluded that the Sundanese language teaching material with the title